2016
DOI: 10.1111/josi.12158
|View full text |Cite
|
Sign up to set email alerts
|

Old and Unemployable? How Age‐Based Stereotypes Affect Willingness to Hire Job Candidates

Abstract: Across the world, people are required, or want, to work until an increasingly old age. But how might prospective employers view job applicants who have skills and qualities that they associate with older adults? This article draws on social role theory, age stereotypes and research on hiring biases, and reports three studies using age‐diverse North American participants. These studies reveal that: (1) positive older age stereotype characteristics are viewed less favorably as criteria for job hire, (2) even whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 33 publications
3
109
2
4
Order By: Relevance
“…In addition, hiring decisions about older people may depend on the job type. For example, previous research has shown that age-related hiring bias may differ in relation to whether the job role is of low or high status (Abrams et al, 2016). Varying candidates’ profiles as well as investigating different types of jobs can help to understand the complex interplay between job candidate, job type, and decision-maker during hiring decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hiring decisions about older people may depend on the job type. For example, previous research has shown that age-related hiring bias may differ in relation to whether the job role is of low or high status (Abrams et al, 2016). Varying candidates’ profiles as well as investigating different types of jobs can help to understand the complex interplay between job candidate, job type, and decision-maker during hiring decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Abrams, Swift, and Drury () also make a unique contribution to this line of inquiry by examining characteristics that are associated with younger versus older workers. In pilot work, they determined characteristics associated with younger workers (e.g., learning new skills, being creative) and older workers (e.g., dealing with people politely, carefulness).…”
Section: Subthemes In the Expansion Of The Understanding Of Ageismmentioning
confidence: 99%
“…However, analyses of legal claims (von Schrader and Nazarov, 2015), workforce surveys (e.g., Kelly Services, 2006), and experimental as well as field studies (e.g., Gordon and Arvey, 2004; Bal et al, 2011) suggest that organizations have not yet reached this goal: discrimination against older workers is prevalent, particularly at hiring. In fact, organizations are reluctant to invest in older workers (North and Fiske, 2016) and show bias in hiring older workers (Abrams et al, 2016), especially older female workers (Neumark et al, 2015). Often, the age bias goes back to negative stereotypes about older workers that are activated when recruiters learn about the age of the job candidate (Perry et al, 1996; Shore and Goldberg, 2005).…”
Section: Introductionmentioning
confidence: 99%